RESPON TANAMAN BAYAM MERAH (Amaranthus tricolor L.) TERHADAP PERBEDAAN KONSENTRASI GANDASIL D DAN JENIS SUMBU SECARA HIDROPONIK - Pambudi, Setyo; Ritawati, Sri; Roidelindho, Kiki; Romdhonah, Yayu (Fakultas Pertanian Universitas Mataram, 2024)
The increasing demand for vegetables is not matched by the expansion of agricultural land, hydroponic farming systems is a perfect solution to solve this problem. Using Gandasil D fertilizer can help plants to imporve the quality of production, especially in the leaf part. This research aims to determine the response of red amaranth (Amaranthus tricolor L.) to the different concentrations of Gandasil D fertilizer and wick types in hydroponic system using the wick system method. The experimental design used in this study was a Factorial Randomized Block Design (RBD) consisting of two factors. The first factor was the concentration of Gandasil D fertilizer, there were four levels of concentration: 0 g/L, 2 g/L, 3 g/L, and 4 g/L. The second factors was the type of wick, which consisted of three levels: stove wick, flannel wick, and wool wick. The results is Gandasil D fertilizer at 2 g/L significantly increased plant height at 21 and 28 Days After Sowing (DAS), measuring (12,94 cm) and (18,53 cm). The application of Gandasil D fertilzer at 4 g/L produced the highest results for fresh and dry weight at (13,80 grams) and (9,58 grams).